(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
يهدف البحث الحالي إلى التعرف على جودة الحياة وعلاقتها بتقدير الذات لدى طلبة قسمي علم النفس والإرشاد النفسي في كلية التربية بجامعة دمشق، حسب متغيرات الجنس (ذكر، أنثى)، والتخصص الدراسي (علم النفس، الإرشاد النفسي(، لدى عينة البحث. وقد تم استخدام مقياس جودة الحياة لطلبة الجامعة من إعداد (منسي وكاظم 2006)، ومقياس تقدير الذات من إعداد (فاكهة جعفر 2007). وبلغ عدد أفراد العينة ككل (100) بينهم (50) من طلبة قسم علم النفس و(50) من طلبة قسم الإرشاد النفسي، وقد توصلت الدراسة إلى النتائج الآتية : 1- لا توجد علاقة ارتباطية ذات دلالة إحصائية بين جودة الحياة وتقدير الذات لدى أفراد عينة البحث. 2- لا توجد فروق تبعاً للجنس في جودة الحياة. 3- لا توجد فروق تبعاً للتخصص الدراسي في جودة الحياة. 4- لا توجد فروق تبعاً للجنس في تقدير الذات. 5- لا توجد فروق تبعاً للتخصص الدراسي في تقدير الذات. The current research aims to identify the self-esteem and its relationship to the quality of life among the students of sections of psychology and psychological counseling in the College of Education at the University of Damascus, according to the variables of gender (male, female), and a course of study (psychology, psychological counseling (to identify the relationship between self-esteem and quality life in a sample search I have been using a measure of the quality of life for the students of the University of preparation (and forgotten Kazim 2006) and a measure of self-esteem, Dr. preparation (fruit Jaafar 2007). The number of members of the sample as a whole (100), including 50 of the students in the Department of Psychology and (50) students in the Department of Psychological Guidance. The study found the following results: 1- No correlation statistically significant differences between the quality of life and self-esteem among the members of the research sample. 2- There were no differences by sex in the quality of life. 3- There are no differences depending on the specialization course in quality of life. 4- There were no differences by sex in self-esteem. 5- There are no differences depending on the specialization course in self-esteem.